(untitled) (Scientific journal of the Fergana State University, 2023)
This article shows the methods of preparing future teachers for the design of innovative pedagogical technologies. Designing educational activities in the pedagogical technology system, the teacher in designing an educational activity, analyzing the teaching process, teaching results, teaching students to independent thinking, independent reading, creative analysis of knowledge It is important to create a methodical system for teaching, to turn acquired knowledge into skills, to develop the content of knowledge, skills and qualifications that students should acquire.